ESI‐TOF mass spectrometry of cationic carbosilane dendrimers: A potent tool for characterization of structural defects. (16th August 2018) - Cuřínová, Petra; Krupková, Alena; Červenková Šťastná, Lucie; Müllerová, Monika; Čermák, Jan; Strašák, Tomáš
Abstract: Macromolecular polyelectrolytes are gaining considerable attention for the application in medicine that implies their detailed characterization. We have successfully applied electrospray ionization mass spectrometry (ESI MS) to the analysis of defects in the structure of three generations of polycationic carbosilane dendrimers bearing series of quarternary phosphonium groups at their periphery. Besides expected defects caused by incomplete conversion of particular reaction steps during the synthesis of dendritic scaffold and subsequent peripheral functionalization, also, several products of side reactions were observed together with defects created in the course of measurement (particularly ion exchange products). Defective molecules can be to some extent separated by means of gel permeation chromatography that proves that they are not products of in source fragmentation processes. Within the reaction sequence used for the synthesis of dendrimers under study, hydrosilylation was the source of most defects; the effectivity of quarternization depends on the type of phosphine. Results confirm high sensitivity of ESI MS towards defects, stability of the carbosilane skeleton towards fragmentation under the conditions of ESI ionization, and capability to detect both lower‐ and higher‐molecular weight impurities arising from the synthetic sequence in the same m/z range as the target dendrimer, thus providing valuable view of the polydispersity.